LITERATURE REVIEW MANFAAT SENAM LANSIA TERHADAP KUALITAS HIDUP LANSIA - Handayani, Sri Puzzy; Sari, Rina Puspita; Wibisono, Wibisono (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2020)
ABSTRACTIntroduction: 52.31% of the number of health complaints in elderly women is higher than the percentage of elderly men is 49, 74%. Changes that occur in the elderly tend to decrease in physical, psychological, psychosocial systems. This requires an action activity that can reach all aspects of the decline that is by doing elderly gymnastics. The purpose of this research to identify the benefits of elderly exercise on the quality of life of the elderly. Research methods by using literature review as a guide to search for research articles obtained from the internet using the Science Direct site, and Google Scholar. The results analysis of 10 selected research articles shows that elderly exercise can have several benefits, namely: physical benefits can improve physical fitness, body balance, breathing, and decreased blood pressure in elderly hypertension. Psychological benefits can improve sleep quality, decrease insomnia levels, decrease depression levels, reduce stress levels, and manage pain. Social and environmental benefits. Elderly exercise 3 times a week with a minimum duration of 30 minutes and a maximum of 40 minutes with a time of> 4 weeks will be more effective in getting many benefits.